Vulnerability of xylem to embolism in relation to plant hydraulic resistance in Quercus pubescens and Quercus ilex co-occurring in a Mediterranean coppice stand in central Italy - Tognetti, R; Longobucco, A; Raschi, A (New Phytologist, 1998)
The seasonal patterns of xylem embolism and xylem transport properties in Quercus pubescens Willd. and Quercus ilex L. trees growing in a natural mixed coppice stand in conditions of severe water stress were investigated. Xylem embolism was evaluated in both dehydrating branches and in apical twigs during a whole year. Measurements of xylem water potential were conducted from predawn to sunset on selected sunny days. On the same days, diurnal courses of leaf conductance were monitored. Measurements of half-hourly sap flow were made by the heat-pulse technique throughout the summer. At the onset of summer, a sharp decrease in water potential was observed in both species. Full recovery of water potentials was observed for both species after the first major rainfall event in September. Both experienced serious embolism throughout the year, ranging between minima of c. 60% (expressed as percentage loss of hydraulic conductivity) after the rains in autumn and after bud burst in spring, and maxima of c. 80% during summer and after freezing-thawing events during the winter season. A significant negative linear relationship was found between water potential and xylem embolism in branches dehydrating in air for Q. pubescens and Q. ilex. Q. pubescens had greater efficiency in hydraulic transport (higher specific conductivity and leaf specific conductivity) by the xylem than Q. ilex. In June, leaf conductance was high early in the morning and decreased gradually during the day. Midday depression of leaf conductance, as a result of high evaporative demand combined with water deficit, was observed in both species. In August, leaf conductance of both species was greatly reduced, as water potential dropped to extremely low values, and the stomata were almost completely closed during the afternoon. No hysteresis resulting from plant capacitance was observed in the relationship between shoot water potential and sap flow. Q. pubescens exhibited very high values of whole-tree hydraulic resistance between July and September, whereas Q. ilex generally showed lower values. The effect of soil moisture depletion on the relationship between sap flow and shoot water potential appears as a lowering of water potential at zero flow. A significant decrease of whole-tree hydraulic resistance in both species was observed with the onset of the autumn, preceding the partial recovery of twig hydraulic conductivity. The results demonstrate that both Q. pubescens and Q. ilex, although highly tolerant of severe water stress and tissue dehydration, operate at the limits of safety which are surpassed under severe droughts, and prolonged climatic stress might predispose these Quercus species to decline.
Keywords: cavitation; Drought; Hydraulic resistance; Quercus ilex L.; Quercus pubescens Willd.; water relations; xylem embolism

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - LO GULLO, M A; Salleo, S (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - Lo Gullo, M. A.; Salleo, S. (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism